Hubungan Pembelajaran Daring dengan Tingkat Stres pada Mahasiswa MIK di STIKes Santa Elisabeth Medan - Indah Boni Yolanda Pardede; Elsa Indriani Purba (Jurnal Pendidikan dan Pembelajaran, 2022)
Covid-19 has hit all parts of the world, one of which is Indonesia, Covid is a contagious disease from person to person so it can spread quickly, directly or indirectly. This Covid-19 condition attacks the respiratory system, at that time there were no outbreak handlers, vaccines, medicines for healing Covid-19 patients and no way to break the chain of spread. The government's policy is to carry out physical distancing, lock down, PPKM, the impact of these government policies will certainly hamper various growths such as economic, social, and education. This research uses cross sectional research. The research instrument was 47 students of Health Information Management STIKes Santa Elisabeth Medan, sampling was carried out using total sampling technique, data collection was carried out by primary data. Data analysis using SPSS. The results of statistical tests using the chi-square test obtained a p-value of 0.001 seen from Asymp.Sig (2-sided) p<0.05. online learning for students of Health Information Management study program at STIKes Santa Elisabeth Medan in good category as many as 37 respondents (78.7%), stress levels in Health Information Management students at STIKes Santa Elisabeth Medan in medium category as many as 28 respondents (59.6%). Suggestions for students to avoid stress while participating in online learning are by starting to realize and pay attention to themselves so they don't experience stress. Suggestions for future researchers to get a broader picture